Poverty Alleviation Of Farmers Through Institutional Role Of Farmers In Pamekasan Regency - Mohammad - Wahed; Wirya Wardaya (Trunojoyo University of Madura, 2022)
The purpose of this study is to find out the factors that cause poverty in farmers, the programs and policies that farmers need most, as well as how the institutional role of farmers in poverty alleviation of farmers with the analysis method Ziel Orientierte Projekt Planung (ZOPP). The data used is sourced from secondary and primary data. the results in this study concluded that: 1) poverty in the farming community due to low income farmers as a result of government policy has not been fully propetani; 2) the main program priorities to achieve the welfare of the peasant community, namely: a) the program of market creation for farmers through the purchase of agricultural products by the government and the creation of improved skills to farmers in order to create high quality products; and b) mentoring programs for farmer groups through organizational management training and the ability to perform external functions (Networking); and 3) While the institutional role of farmers as a means to realize the expectations, desires, and fulfillment of the needs of farmers. Effective farmer institutions are expected to make a real contribution in improving independence and well-being in farmers' lives.